(untitled) (Physical Education, Health and Social Sciences, 2026)
Pakistan’s agri-business industry is one of the most the most essential components of the domestic economy. It accounts for the approx. 22.9 % of the GDP. It also provides employment to about 37 to 40% of the domestic labor force. The sector has been grappling with a variety of short-term growth opportunities and long-term volatility, e.g. 6.3% growth in FY 2023/2024. The author of this paper critically reassesses the input, support polices of the country, especially fertilizer, water (Abiana) and tube-well energy subsidies. Such policies, while significantly contributing to the fiscal deficit, aggravate the circular debt, which is projected to reach Rs. 2.47 trillion by May 2025, and provide little to no productivity increases. Empirical data shows very low growth elasticity of fertilizer subsidies (4.3% for wheat and 6.1% for rice for each 1% increase in subsidy), significant underperformance of subsidy mechanisms with little benefits to households (average Rs. 74/month for a family of five), and significant water wastage (38% of canal water is unutilized), excessive groundwater extraction, and low recovery of irrigation SE. Initiatives like the Punjab Kissan Card program have boosted overall input usage (increased urea sales by 57.9%) and while seed sector reforms and solarization efforts are promising, other issues of counterfeit seeds and unmoderated impacts of solar grids remain. Advocating for lessons from India (that is, Direct Benefit Transfer savings), along with Vietnam and Brazil, the analysis speaks to the need to move from indiscriminate, distortionary subsidies to precise, digital, market-facilitated subsidies and supports, complemented by enhanced targeted R&D in climate-smart agriculture, precision farming technologies, along with the requisite institutional reforms to construct resilience, sustainability, and productive farming in a climate and fiscally constrained world.